The Future of Robotic Surgery in Pediatric Urology: Upcoming Technology and Evolution Within the Field - Sheth, Kunj R.; Koh, Chester J. (Frontiers in Pediatrics, 2019)
Since the introduction of the Da Vinci Surgical System (Intuitive Surgical, Inc., Sunnyvale, CA) in 1999, the market for robot assisted laparoscopic surgery has grown with urology. The initial surgical advantage seen in adults was for robotic prostatectomy, and over time this expanded to the pediatric population with robotic pyeloplasty. The introduction of three-dimensional visualization, tremor elimination, a 4th arm, and 7-degree range of motion allowed a significant operator advantage over laparoscopy, especially for anastomotic suturing. After starting with pyeloplasty, the use of robotic technology with pediatric urology has expanded to include ureteral reimplantation and even more complex reconstructive procedures, such as enterocystoplasty, appendicovesicostomy, and bladder neck reconstruction. However, limitations of the Da Vinci Surgical Systems still exist despite its continued technological advances over multiple generations in the past 20 years. Due to the smaller pediatric market, less focus appears to have been placed on the development of the smaller 5 mm instruments. As pediatric urology continues to utilize robotic technology for minimally invasive surgery, there is hope that additional pediatric-friendly instruments and components will be developed, either by Intuitive Surgical or one of the new robotic platforms in development that are working to address many of the shortcomings of current systems. These new robotic platforms include improved haptic feedback systems, flexible scopes, easier maneuverability, and even adaptive machine learning concepts to bring robotic assisted laparoscopic surgery to the next level. In this report, we review the present and upcoming technological advances of the current Da Vinci surgical systems as well as various new robotic platforms, each offering a unique set of technological advantages. As technology progresses, the understanding of and access to these new robotic platforms will help guide pediatric urologists into the next forefront of minimally invasive surgery.